Development of a Model for Comprehensive Evaluation of Corporate Resilience Against Disasters (1)—An Examination Based on Indicators Developed by “Resilient Organisations” - Tashiro, Kuniyuki; Kitago, Yoko (Journal of disaster research, 2024)
“Resilience” is the ability to recover after being affected by a disaster or accident. Companies are expected to be resilient against accidents and disasters; however, no method comprehensively evaluates corporate resilience. As a preparation for developing such an evaluation method, this study examines the 13 Resilience Indicators developed by “Resilient Organisations” as one of the models for organizational resilience to assess whether it comprehensively covers the factors that contribute to corporate resilience. This study compares the indicators with past accidents and disaster cases. Consequently, the study determined that the 13 Resilience Indicators do not explicitly cover the following four factors: (1) risk diversification related to external resources such as suppliers, (2) prompt decision-making and action, (3) countermeasures to protect corporate reputation, and (4) a never-give-up attitude. It cannot be said that this is a definitive conclusion, as subjectivity intervenes in various ways in the examination process. However, this study identified factors that should be considered while developing a model that comprehensively includes factors that contribute to corporate resilience.